Some taxonomic and nomenclatural changes in American Mantodea (Insecta, Dictyoptera)—Part I - Agudelo, Antonio A.; Rivera, Julio (Zootaxa, 2015)
Multiple nomenclatural problems persist in mantodean taxonomy. This constitutes an important challenge for praying mantis systematics, its forthcoming development and future consolidation. In this first contribution, we attempt solving a number of issues involving mostly Neotropical praying mantis species described by Brazilian entomologists Paulo S. Terra, Cândido F. de Mello-Leitão, Salvador de Toledo Piza Junior and Lauro J. Jantsch. We provide evidence to justify the following nomenclatural changes. In Acanthopidae, Acontiothespis travassosi Jantsch, 1986 is a new synonym of Raptrix perspicua (F. 1787). Changes in Thespidae are: Emboicy Terra, 1982 is a new synonym of Chloromiopteryx Giglio-Tos, 1915, E. mirim Terra, 1982 is transferred to Chloromiopteryx as C. mirim (Terra, 1982) (new combination); Musoniola plurilobata Mello-Leitão, 1937 is transferred to Chloromiopteryx as C. plurilobata (Mello-Leitão, 1937) (new combination); Metathespis modesta Piza, 1968 is removed from synonymy with Chloromiopteryx thalassina (Burmeister, 1838) and considered valid as C. modesta (Piza, 1968) (new combination and status revalidated); Metathespis precaria Piza, 1968 is removed from synonymy with Chloromiopteryx thalassina (Burmeister, 1838) and considered a new synonym of Miobantia rustica (Fabricius, 1781); Eumiopteryx magna Jantsch, 1991 is transferred to Anamiopteryx as A. magna (Jantsch, 1991) (new combination). For Mantidae/Amelinae, Tithrone corseuli Jantsch, 1986 and T. clauseni Jantsch, 1995 are new synonyms of Litaneutria minor (Scudder, 1872); in Mantidae/Photininae Coptopteryx gigliotosi Piza, 1960 (non Werner, 1925), its replacement name Coptopteryx ermannoi Jantsch & Corseuil, 1988 and Paraphotina precaria Piza, 1966 (the latter currently placed within Coptopteryx) are all new synonyms of Coptopteryx argentina (Burmeister, 1838), whereas Brachypteromantis bonariensis Piza 1960 (currently placed among Coptopteryx) is a new synonym of Coptopteryx gayi (Blanchard, 1851); Tithrone major Piza, 1962 is transferred to Orthoderella as O. major (Piza, 1962) (new combination); Orthoderella brasiliensis Roy & Stiewe, 2011 is a new synonym of Orthoderella major (Piza, 1962); Tithrone catharinensis Piza, 1962 is a new synonym of Photina vitrea (Burmeister, 1838); Margaromantis Piza, 1982, Rehniella Lombardo, 1999, Colombiella Koçak & Kemal, 2008 and Lombardoa Özdikmen, 2008 are all new synonyms of Photiomantis Piza, 1968 (status revalidated); Metriomantis planicephala Rehn 1916 is transferred to Photiomantis as P. planicephala (Rehn, 1916) (new combination) and Photiomantis silvai Piza, 1968 is considered a new synonym of Photiomantis planicephala (Rehn, 1916);  Margaromantis nigrolineata Menezes & Bravo, 2015 is transferred to Photiomantis as P. nigrolineata (Menezes & Bravo, 2015) (new combination). In Mantidae/Vatinae, Uromantis amazonica Jantsch, 1985 and Uromantis paraensis Jantsch, 1985 (currently placed among Stagmomantis), are new synonyms of Chopardiella latipennis (Chopard, 1911), while Pseudovates hyalostigma Mello-Leitão, 1937 and Vates obscura Toledo Piza, 1983 are new synonyms of V. biplagiata Sjöstedt, 1930. Lectotypes are designated for Chloromiopteryx thalassina (Burmeister, 1838) and Orthoderella major (Piza, 1962). Finally, we provide supplementary information about the works of S. de T. Piza and L. J. Jantsch, and a necessary critical assessment of their taxonomic contributions to the Mantodea.